Examination of the polyphenol content and bioactivities of Prunus spinosa L. fruit extracts - Veličković, Ivona; Žižak, Željko; Rajčević, Nemanja; Ivanov, Marija; Soković, Marina; Marin, Petar D.; Grujić, Slavica (Archives of Biological Sciences, 2020)
Paper description: P. spinosa (blackthorn) aqueous, ethanol and acetone fruit extracts were analyzed. Total phenolic and flavonoid contents, the anthocyanin profile and bioactivities were determined by in vitro colorimetric methods. P. spinosa fruit extracts exhibited antioxidant, antimicrobial and anti-diabetic properties with the ethanol fruit extract markedly inhibiting α-glucosidase, an enzyme-linked with diabetes mellitus type II. P. spinosa fruit extracts, in particular the ethanol extract, should be considered for further investigation of naturally occurring compounds with a potential anti-diabetic effect. Abstract: We investigated the total phenolic and flavonoid contents and the anthocyanin profiles in aqueous, ethanol and acetone extracts of Prunus spinosa (Rosaceae) fruit, and their antioxidant, antibacterial, antifungal, antidiabetic and antitumor properties. The contribution of polyphenol contents to the bioactivity of the extracts was calculated and observed through Pearson’s coefficient of correlation. The acetone extract was the richest in phenols and anthocyanins and the ethanol extract in flavonoids. Cyanidin was the most abundant anthocyanin compound in all examined extracts. The ethanol extract showed the most promising antioxidant activity in DPPH, ABTS and FRAP assays. Tested bacteria were more affected by the ethanol than by the aqueous extract. Both the ethanol and aqueous extracts exhibited potential antidiabetic effects, observed as inhibition of α-amylase and α-glucosidase, enzymes linked with diabetes mellitus type II. The ethanol extract was a potent α-glucosidase-inhibitor with a significantly lower IC50 value than the positive control, glucobay, used to treat diabetes mellitus type II. Neither the ethanol nor the aqueous extracts had any effects on tested human malignant cell lines. Our results indicate that the ethanol extract showed the most pronounced in vitro antioxidant and antimicrobial effects, and a potential antidiabetic activity, which can be ascribed to its high flavonoid content. Our results indicate that research of compounds, particularly of flavonoids present in the ethanol extract and their anti-diabetic properties should be examined further. https://doi.org/10.2298/ABS191217004V Received: December 17, 2019; Revised: February 7, 2020; Accepted: February 8, 2020; Published online: February 10, 2020 How to cite this article: Veličković I, Žižak Ž, Rajčević N, Ivanov M, Soković M, Marin P, Grujić S. Examination of the polyphenol content and bioactivities of Prunus spinosa L. fruit extracts. Arch Biol Sci. 2020;72(1):105-15.